Correction to: Neural dynamics based complete grid coverage by single and multiple - Arindam Singha; Anjan Kumar Ray; Arun Baran Samaddar (SN Applied Sciences, 2021)
A correction to this paper has been published: https://doi.org/10.1007/s42452-021-04606-4